2014
DOI: 10.1371/journal.pone.0112397
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Cranial Irradiation-Induced Cerebrovascular Damage Is Reversible in Mice

Abstract: BackgroundHigh-dose radiation-induced blood-brain barrier breakdown contributes to acute radiation toxicity syndrome and delayed brain injury, but there are few data on the effects of low dose cranial irradiation. Our goal was to measure blood-brain barrier changes after low (0.1 Gy), moderate (2 Gy) and high (10 Gy) dose irradiation under in vivo and in vitro conditions.MethodologyCranial irradiation was performed on 10-day-old and 10-week-old mice. Blood-brain barrier permeability for Evans blue, body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 77 publications
2
43
1
Order By: Relevance
“…In the juvenile rat brain, we found that BBB disruption after irradiation varies among brain regions and that the cerebellum is the most sensitive region to irradiation in this respect. This finding is in line with another study demonstrating BBB disruption 1 week and 4 weeks post irradiation in the cerebellum of both juvenile and adult mouse brains7. However, BBB integrity in the cerebrum was only disrupted after 1 week and in the adult brain and after 4 weeks in the juvenile brain indicating that the cerebellar BBB is more sensitive to cranial irradiation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the juvenile rat brain, we found that BBB disruption after irradiation varies among brain regions and that the cerebellum is the most sensitive region to irradiation in this respect. This finding is in line with another study demonstrating BBB disruption 1 week and 4 weeks post irradiation in the cerebellum of both juvenile and adult mouse brains7. However, BBB integrity in the cerebrum was only disrupted after 1 week and in the adult brain and after 4 weeks in the juvenile brain indicating that the cerebellar BBB is more sensitive to cranial irradiation.…”
Section: Discussionsupporting
confidence: 92%
“…Radiation-induced endothelial cell death is of crucial importance for the development of brain injury3536 since this may lead to structural changes in blood vessels, decreased blood vessel density and length, and increased vessel permeability737. In the current study we observed that cranial irradiation to the juvenile rat resulted in a lack of growth of the cerebellum, both in the gray and white matter.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…58,59 P-glycoproteins which remove foreign substances from the brain back to the blood circulation are expressed exclusively by the ECs of the blood brain barrier (BBB). The albumin permeability across the BBB was found to be 25-fold lower than that of the pulmonary microvascular beds (0.043 Â 10 À6 cm s À1 ), 82 aptly illustrates the restrictive nature of this understandably restrictive bed to protect a privileged organ, the brain. 40,61 In addition to the exclusive expression of these specific biomarkers, the endothelium bed heterogeneity is defined by differential or uneven expression pattern of the commonly shared ECs biomarkers.…”
Section: Ecs Heterogeneity In Healthy Vascular Bedsmentioning
confidence: 93%